(untitled) (Damascus University Journal of agriculture sciences, 2021)
In a scene reflectance, spectral values ​​of different green vegetation areas that integrated with the soil (0, 25, 50, 75 and 100% green vegetation cover of a scene reflectance Area) were studied. Red and near-infrared bands according to the values ​​of each of radiance and Reflectance were used, and then applied in the vegetation indices NDVI and RVI. The aim is improving the accuracy of estimating the plant vegetation from the spectral data of the reflectance ​​ scene. The relationships between red and near infrared spectrum for both radiance and reflectance in the pure scene area either bare soil (0% vegetation ) or complete green area (100% vegetation) were a linear positive trend. While, the relationships with the different areas (25, 50, 75% vegetation) were linear negative trend that also similar to the general linear passive trend (which built according to all percent vegetation probability). Results refer in accuracy estimation the green areas by spectral data should be: studying from general up to detailed case, calibration the spectral components of the vegetation indices, and applying the vegetation indices (as NDVI) which more better under various soils